Impact of maternal ART on mother-to-child transmission (MTCT) of HIV at six weeks postpartum in Rwanda - Placidie Mugwaneza; Alexandre Lyambabaje; Aline Umubyeyi; James Humuza; Landry Tsague; Fabian Mwanyumba; Vincent Mutabazi; Sabin Nsanzimana; Muhayimpundu Ribakare; Ange Irakoze; Emmanuel Mutaganzwa; Carl Lombard; et al. (BMC, 2018)
Abstract Background In 2010, Rwanda adopted ART for prevention of mother to child transmission of HIV from pregnant women living with HIV during pregnancy and breasfeeding period. This study examines rates of mother-to-child-transmission of HIV at 6-10 weeks postpartum and risk factors for mother-to-child transmission of HIV (MTCT) among HIV infected women on ART during pregnancy and breastfeeding. Methods A cross-sectional survey study was conducted between July 2011-June 2012 among HIV-exposed infants aged 6-10 weeks and their mothers/caregivers. Stratified multi-stage, probability proportional to size and systematic sampling to select a national representative sample of clients. Consenting mothers/caregivers were interviewed on demographic and program interventions. Dry blood spots from HIV-exposed infants were collected for HIV testing using DNA PCR technique. Results are weighted for sample realization. Univariable analysis of socio-demographic and programmatic determinants of early mother-to-child transmission of HIV was conducted. Variables were retained for final multivariable models if they were either at least of marginal significance (p-value < 0.10) or played a confounding role (the variable had a noticeable impact > 10% change on the effect estimate). Results The study sample was 1639 infants with HIV test results. Twenty-six infants were diagnosed HIV-positive translating to a weighted MTCT estimate of 1.58% (95% CI 1.05-2.37%). Coverage of most elimination of MTCT (EMTCT) program interventions, was above 80, and 90.4% of mother-infant pairs received antiretroviral treatment or prophylaxis. Maternal ART and infant antiretroviral prophylaxis (OR 0.01; 95%CI 0.001-0.17) and maternal age older than 25 years were significantly protective (OR 0.33; 95%CI 0.14-0.78). No disclosure of HIV status, not testing for syphilis during pregnancy and preterm birth were significant risk factors for MTCT. Factors suggesting higher socio-demographic status (flush toilet, mother self-employed) were borderline risk factors for MTCT. Conclusion ART for all women during pregnancy and breastfeeding was associated with the estimated low MTCT rate of 1.58%. Mothers who did not receive a full package of anti-retroviral therapy according to the Rwanda EMTCT protocol, and young and single mothers were at higher risk of MTCT and should be targeted for support in preventing HIV infection.